2019
DOI: 10.1159/000496173
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Efficacy of Holmium Laser Enucleation of the Prostate in Treating Prostate Volumes of ≤80 and > 80 mL

Abstract: Introduction: Holmium laser enucleation of the prostate (HoLEP) is becoming the new standard procedure for treating benign prostatic hyperplasia (BPH), a common condition in aging men. Most studies have focused on proving its efficacy in treating large prostates. In this study, we compared its efficacy in treating small (< 80 mL) and large (> 80 mL) prostates. Methods: This prospective study included 119 patients with BPH who underwent HoLEP by the same surgeon between June 2015 and December 2017. They were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 20 publications
(38 reference statements)
2
6
0
Order By: Relevance
“…Holmium laser enucleation of the prostate surgery, which is accepted as feasible and safe ‘size‐independent’ surgical treatment of BPH in both AUA and EAU guidelines, has gained the popularity it deserves, and publications on this subject are rapidly increasing (Das et al., 2019; Foster et al., 2018; Gratzke et al., 2015). There are several studies in the literature, assessing the efficacy of BPH and holmium laser treatment surgeries according to prostate size; however, these studies compare large prostates to small‐ and medium‐sized prostates together, or small prostates to medium and large prostates together, or small and moderate prostates together to large prostates(Gazel et al., 2019; Glybochko et al., 2017; Park et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Holmium laser enucleation of the prostate surgery, which is accepted as feasible and safe ‘size‐independent’ surgical treatment of BPH in both AUA and EAU guidelines, has gained the popularity it deserves, and publications on this subject are rapidly increasing (Das et al., 2019; Foster et al., 2018; Gratzke et al., 2015). There are several studies in the literature, assessing the efficacy of BPH and holmium laser treatment surgeries according to prostate size; however, these studies compare large prostates to small‐ and medium‐sized prostates together, or small prostates to medium and large prostates together, or small and moderate prostates together to large prostates(Gazel et al., 2019; Glybochko et al., 2017; Park et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Although HoLEP is addressed as a surgical treatment option of small prostate flow chart in AUA guidelines, it is still stayed behind transurethral incision of the prostate and transurethral resection of the prostate (TURP) for small prostate treatment options in EAU guidelines (Foster et al., 2018; Gratzke et al., 2015). The effect of prostate size on the outcome of HoLEP surgery has been studied in the literature; most of the published papers compared the large prostates above 80 or 100 ml (Gazel et al., 2019; Glybochko et al., 2017; Hettiarachchi et al., 2002; Jones et al., 2016; Kuntz et al., 2008; Zhang et al., 2020) and some compared small prostates below 40 or 30 ml (Kim et al., 2016, 2019; Park et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Prolonged operation time is associated with an increase in the risk of complications such as bleeding, surgical site infection, venous thromboembolism, or cardiac, neurologic, and respiratory problems, and this might be important especially in the treatment of comorbid patients [11]. The optimal surgical method should provide the maximum removal of the prostate with fewer complications [13]. Therefore, knowing the amount of prostate that can be removed in a particular time by a procedure and how the total duration of this procedure changes depending on prostate volume might be important in terms of deciding the patient’s anaesthesia method and even the type of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our correlation analysis demonstrated a relationship between prostate volume and operation time of HOLEP. As it is known, HoLEP consists of 2 steps: enucleation and morcellation, and the volume of the prostate does not affect the enucleated tissue weight per minute [13]. In addition, it was reported that the surgical experience not to affect the duration of morcellation, but to shorten the enucleation and total operation time [17].…”
Section: Discussionmentioning
confidence: 99%
“…In the recent years, holmium laser enucleation of the prostate (HoLEP) has become a main surgical option for treatment of lower urinary tract symptoms due to benign prostatic enlargement when surgical therapy is indicated [1]. In contrast to transurethral resection of the prostate (TURP) and open simple prostatectomy, it can be performed size independently and with lower morbidity [2, 3]. Moreover, apart from similar functional long-term outcomes [4], our group reported a higher prostate cancer detection rate by HoLEP than TURP [5].…”
Section: Introductionmentioning
confidence: 99%